Evaluation on Rust Stabilizer Paint for Maintenance Painting of Internal Pipeline - Mohd Isa, Ahmad Safwan Bin (Universiti Teknologi PETRONAS, 2009)
Maintenance painting is important in order to reduce the further damage to the equipment from corrosion attack. The challenge is what type of paint that can work properly under minimum surface preparation especially for internal pipeline surface during maintenance painting. The main objective of this project is to evaluate the rust stabilizer paint performance which will be applied for internal pipelines coating for maintenance purpose. The methodologies to evaluate the paint performance are pull-off adhesion test (ASTM D4541) to test the paint strength, Taber abrasion test (ASTM D4060) to test paint wear index, salt spray test (ASTM B117) to test the paint corrosion protection barrier level and immersion test (ASTM D870) to test water and petrol absorption rate. The result from pull-off adhesion test is 967 psi. For the Taber abrasion test, the wear index obtained is 7.28 x 10-5 g/rev for 1000 revolutions with 1000 g loads. For the salt spray test, there is no significant defect after 336 hours of exposure. For the immersion test, 0.21% weight increased for water immersion and 0.88% weight increased for petrol immersion after 500 hours of immersion. As a conclusion, the tests conclude that the technical specification is met to apply rust stabilizer paint at internal pipeline surface during maintenance painting. Further study need to be done to ensure the capability of the paint to convert rust into stabilizes components for benefits of industrial application.